NATURE-RESOURCE POTENTIAL OF NATURAL REGIONS OF UKRAINE IN PRESENT-DAY FIGURES - Rudenko, V.; Rudenko, S. (Екологічні науки : науково-практичний журнал, 2023)
The value of the aggregative nature-resource potential (NRP) of Ukrainian natural regions was as of 01.01.2022 estimated to amount to 1395,543 milliard hryvnyas. Estimation of aggregative NRP previously performed in 2013 in 2004–2008 prices was now figured through indexation of monetary evaluation of mineral, water, land, forest, fauna and natural recreation resources within natural regions of Ukraine. NRP estimation was performed for each of 278 primary natural physic-geographical rayons of Ukraine, 57 oblasts, 14 krays (provincial ecosystems, according to M. Holubets), 3 sub-zones, 4 zones (biomes) and 3 natural countries (two of which representing mountain country ecosystems). It is asserted that the NRP of the East-European Plain has covers over 9/10 of the total cost value of the potential nature resources of Ukraine, while the Crimean Mountains account for less than 2%, and the Ukrainian Carpathians – for 6,4%. The leadership among “provincial ecosystems” (krays) was taken by the Donetsk Kray (in the Steppe Biome) (14,3% out of the whole NRP of Ukraine), followed by the Podilsko-Prydniprovskyy Kray (in the Forest-Steppe Biome) (11,6%), LeftBank-Dnieper-Pryazovskyy Kray (in the Steppe Biome) (10,5%), Dniester-Dnieper Kray (in the Steppe Biome) (9,4%), and the Polissia Kray (in the Mixed Forest Biome) (9,3%), West-Ukrainian Kray (in the Deciduous Forests Biome) (8,2%), Left-Bank-Dnieper Kray (in the Forest-Steppe Biome) (7,8%), mountain country ecosystem Ukrainian Carpathians (6,4%). The aforesaid five provincial ecosystems accumulate over 77% of the potential of nature resources of Ukraine. The least NRP values were observed in the Crimean Mountain Country Ecosystem (1,9%), the Prychornomorsko-Pryazovskyy Provincial Ecosystem (2,8%), the East-Ukrainian Provincial Ecosystem (3,2%), Crimean Steppe (3,9%) the Prychornomorskyy (5,0%) and the Zadonetsko-Donskyy (5,7%) provincial ecosystems. Key words: nature-resource potential, indexation, natural regions of Ukraine.
Keywords: nature-resource potential; natural regions of Ukraine